2018
DOI: 10.1111/1460-6984.12372
|View full text |Cite
|
Sign up to set email alerts
|

Integration of speech and gesture in aphasia

Abstract: The findings suggest that people with aphasia can have difficulty integrating speech and gesture in order to obtain meaning. Therefore, when encouraging communication partners to use gesture alongside language when communicating with people with aphasia, education regarding the types of gestures that would facilitate understanding is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…In language comprehension, iconic gestures can disambiguate lexical meaning of homonyms (Holle & Gunter, 2007), can support comprehension when the speech is degraded (Drijvers & Özyürek, 2017;Holle et al, 2010) and can provide further details useful in building situational models (e.g. if a listener hears a speaker say 'and then I paid' whilst making a writing gesture, the listener can understand that the speaker paid using a cheque; Cocks et al, 2018). Drijvers and Özyürek (2017) further showed that iconic gestures play a more important role than visible mouth patterns in supporting spoken comprehension in noise, but that both cues together can contribute to comprehension.…”
Section: Non-arbitrariness In Language Processingmentioning
confidence: 99%
“…In language comprehension, iconic gestures can disambiguate lexical meaning of homonyms (Holle & Gunter, 2007), can support comprehension when the speech is degraded (Drijvers & Özyürek, 2017;Holle et al, 2010) and can provide further details useful in building situational models (e.g. if a listener hears a speaker say 'and then I paid' whilst making a writing gesture, the listener can understand that the speaker paid using a cheque; Cocks et al, 2018). Drijvers and Özyürek (2017) further showed that iconic gestures play a more important role than visible mouth patterns in supporting spoken comprehension in noise, but that both cues together can contribute to comprehension.…”
Section: Non-arbitrariness In Language Processingmentioning
confidence: 99%
“…This hypothesis is primary supported by neuropsychological cases which reported that abnormal skilled learned purposive movements (limb apraxia) and language disorders (aphasia) are anatomically and functionally dissociable (Kertesz et al, 1984; Papagno et al, 1993; Heilman and Rothi, 2003). However, limb apraxia often co-occuring with Broca’s Aphasia (Albert et al, 2013) and difficulty in gesture-speech semantic integration was reported in aphasic patients (Cocks et al, 2009, 2018). Alongside clinical data, disrupting the activity in both left IFG and middle temporal gyrus (MTG) is found to impair gesture-speech integration (Zhao et al, 2018).…”
Section: Gestures: a Bridge Between Language And Actionmentioning
confidence: 99%
“…39 A gestural approach to aphasia recovery is primarily endorsed as an adjunct to verbal communication and is promoted for its use as a compensatory word retrieval strategy. 35,36 The connection between hand-arm use and language is particularly salient to many in the Deaf community. Unlike hand gesture, Sign Language contains structured and expansive grammatical rules that share many of the same neural substrates as spoken language.…”
Section: Gesture and Sign Languagementioning
confidence: 99%